2005
DOI: 10.1189/jlb.0504310
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIIB stimulation promotes β1 integrin activation in human neutrophils

Abstract: The molecular stimuli involved in receptor-induced integrin activation are still poorly defined. We have investigated the role of receptors for the Fc portion of immunoglobulin G molecules (Fc gammaR) on activation of integrins in human neutrophils. Cross-linking of Fc gammaRIIA induced an increase in surface expression of beta2 integrins but had no effect on beta1 integrins. In contrast, cross-linking of Fc gammaRIIIB not only increased beta2 integrins on the cell surface but also induced beta1 integrin activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 83 publications
2
28
0
Order By: Relevance
“…Confocal microscopy pictures confirm this rapid internalization. An internalization of Fc␥RIIa was previously suggested on the basis of microscopical techniques (63) and radioactivity measurements (64) but was never quantified as we did in the current study. Furthermore in these two previous studies, Fc␥RIIa was described inside the cell after 10 min (62) or 2 min (63) crosslinking.…”
Section: Discussionmentioning
confidence: 57%
“…Confocal microscopy pictures confirm this rapid internalization. An internalization of Fc␥RIIa was previously suggested on the basis of microscopical techniques (63) and radioactivity measurements (64) but was never quantified as we did in the current study. Furthermore in these two previous studies, Fc␥RIIa was described inside the cell after 10 min (62) or 2 min (63) crosslinking.…”
Section: Discussionmentioning
confidence: 57%
“…Because no associated molecules are known for Fc␥RIIIB, it has become difficult to establish a signaling mechanism for this receptor. Despite this, Fc␥RIIIB is clearly capable of inducing several cell responses, including calcium transients (14 -16), actin polymerization (17), activation of integrins (18), and activation of nuclear factors (Ref. 19 and this report).…”
Section: Discussionmentioning
confidence: 99%
“…F(abЈ) 2 fragments of mAb 3G8 were prepared as described (18,24). Briefly, Ab was diluted at 2 mg/ml at pH of 3.5, and pepsin was added at 25 g/ml.…”
Section: Preparation Of F(abј) 2 Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was found that FcγRIIA, but not FcγRIIIB could induce an increase in L-selectin expression [76]. Opposite to this, FcγRIIIB, but not FcγRIIA, was able to activate β1 integrins [77]. In addition, when the major cell response of neutrophils, arguably phagocytosis, was examined, FcγRIIA was the predominant FcγR mediating this response.…”
Section: Each Fcγr Initiates Particular Signaling Pathways That Lead mentioning
confidence: 99%